Beban Kerja Karyawan Resepsionis Di Trans Luxury Hotel Bandung - Sutardi, Heri; Grace Arthauli, Natania (JURNAL PARIWISATA VOKASI, 2024)
ABSTRACT This research aims to determine the workload of receptionist employees at Trans Luxury Hotel Bandung. The collection method used is a quantitative method. The data collection technique used was by distributing questionnaires and observing. Meanwhile, the data analysis technique uses a Likert scale. Problems in research: a.) 1. What are the physical demands of receptionist employees at The Trans Luxury Hotel Bandung b.) 2. What are the job demands of receptionist employees at The Trans Luxury Hotel Bandung. Suggestions given for solving problems are: Work load has a very physical and mental impact Receptionist employees at The Trans Luxury Hotel Bandung, if physical and mental conditions improve, the quality of employee work will be better. Therefore, the author suggests to companies to hold activities that can refresh the minds and physical bodies of their employees. And secondly, workload assignments. The distribution of work tasks to employees should be given evenly so that excessive workload does not occur, if the number of tasks given to employees is balanced with number of employees, then there will be no imbalance. Employees will also not overtime or exceed their expected working hours. Keywords: Workload, Receptionist